Fluorescent Sensors Based on Organic Polymer-Capped Gold Nanoparticles for the Detection of Cr(VI) in Water - Na Wang; Liangchen Wang; Hong Yang; Tingting Xiong; Shangping Xiao; Jiawen Zhao; Weiping Du (International Journal of Analytical Chemistry)
“Turn-off” fluorescent sensors for Cr(VI) have been fabricated based on organic polymer-capped gold nanoparticles. The fluorescence intensity, as well as the response behavior of the sensors, is dependent on the pH values of buffer solution and dilution amounts of the sensors. When diluted 50 times with pH 2.0 buffer solution, the sensors show good linear responses toward Cr(VI) at concentrations between 2.8–5.9 μM and 5.9–29 μM. The calculated detection limit is 0.63 μM (S/N=3). The interference study and real sample assays exhibit satisfying selectivity and reliability results. Furthermore, the quenched intensity of fluorescence could be recovered by Fe(II) ion, which provides a potential method to detect Fe(II) ions. The quenching and recovering mechanisms have also been investigated. It is suggested that the quenching mechanism is based on the combined effects of internal electron transfer and the inner filter effect. Finally, the recovering mechanism is based on the redox reactions between the Cr(VI) and Fe(II) ions.